2017
DOI: 10.1523/jneurosci.0878-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Loss Increases the Connectivity of Fast Synaptic Motifs and Functional Connectivity in a Developing Hippocampal Network

Abstract: Changes in synaptic strength and connectivity are thought to be a major mechanism through which many gene variants cause neurological disease. Hyperactivation of the PI3K-mTOR signaling network, via loss of function of repressors such as PTEN, causes epilepsy in humans and animal models, and altered mTOR signaling may contribute to a broad range of neurological diseases. Changes in synaptic transmission have been reported in animal models of PTEN loss; however, the full extent of these changes, and their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…1). This finding partially agrees with previous studies in the hippocampus (Chang et al, 2014;Barrows et al, 2017) that reported an increase in GABAergic output upon glutamatergic innervation, suggesting a more general role of glutamatergic input in modulating the degree of inhibition produced by GABAergic neurons. Nevertheless, the modulation by glutamatergic input in the different types of GABAergic neurons manifests in different ways: hippocampal interneurons increased the number of their output synapses, but decreased the presynaptic release efficiency (Chang et al, 2014), whereas striatal GABAergic neurons increased their evoked inhibitory response and vesicle pool size, while maintaining their release efficiency (Fig.…”
Section: Cortical and Thalamic Glutamatergic Neurons Increase Striatasupporting
confidence: 92%
“…1). This finding partially agrees with previous studies in the hippocampus (Chang et al, 2014;Barrows et al, 2017) that reported an increase in GABAergic output upon glutamatergic innervation, suggesting a more general role of glutamatergic input in modulating the degree of inhibition produced by GABAergic neurons. Nevertheless, the modulation by glutamatergic input in the different types of GABAergic neurons manifests in different ways: hippocampal interneurons increased the number of their output synapses, but decreased the presynaptic release efficiency (Chang et al, 2014), whereas striatal GABAergic neurons increased their evoked inhibitory response and vesicle pool size, while maintaining their release efficiency (Fig.…”
Section: Cortical and Thalamic Glutamatergic Neurons Increase Striatasupporting
confidence: 92%
“…A previous imaging study of Dnm1/3 DKO neurons found severely reduced event frequency (Lou et al, 2012), thus, the Dnm1 Ftfl/Ftfl phenotype may represent a milder version of the Dnm1/3 DKO. Other in vitro networks of neurons from DEE-causing gene variants, including Scn1a (Hedrich et al, 2014), GNB1 (Colombo et al, 2019), Kcnt1 (Shore et al, 2020), and Pten (Barrows et al, 2017), have shown increases in activity and/or synchrony, as measured with Ca 2+ imaging or multielectrode arrays. Our results suggest, however, that in Dnm1 Ftfl/Ftfl networks at least, higher order levels of brain architecture are necessary to generate epileptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…At the synaptic level, conditional knockout Pten from GABAergic cortical interneurons increases the synaptic input onto interneurons [ 74 ] and the inhibitory output onto glutamatergic neurons [ 22 , 75 ]. Conversely, a single copy of Pten deletion from PV-neurons impairs the formation of perisomatic inhibition [ 76 ].…”
Section: Discussionmentioning
confidence: 99%